MODEL KENYAMANAN LINGKUNGAN TERMAL DENGAN ELEMEN AIR SEBAGAI MODIFIER IKLIM MIKRO PADA BANGUNAN MAL NIPAH DI MAKASSAR - Syamfitriani Asnur; Muhammad Awaluddin; Syahril Idris; Syamsuddin Mustafa (Pascasarjana Universitas Negeri Makassar, 2021)
The Nipah Mall building was designed by applying the water element in the form of a fish pond and indoor waterfall. This study aims to determine the influence of the water element to control the microclimate inside the Nipah mall building and what factors influence it. The research method used is quantitative with the method of frequency distribution analysis. Data collection was carried out by distributing questionnaires to 200 respondents and taking direct thermal measurements on buildings. The results showed that the rooms in the Nipah Mall were still in a thermally comfortable zone, proving that the element of water has an important role in controlling the microclimate in the spaces in the Nipah Mall building.